2019
DOI: 10.3390/membranes9110143
|View full text |Cite
|
Sign up to set email alerts
|

Composite Nafion Membranes with CaTiO3−δ Additive for Possible Applications in Electrochemical Devices

Abstract: A composite membrane based on a Nafion polymer matrix incorporating a non-stoichiometric calcium titanium oxide (CaTiO3−δ) additive was synthesized and characterized by means of thermal analysis, dynamic mechanical analysis, and broadband dielectric spectroscopy at different filler contents; namely two concentrations of 5 and 10 wt.% of the CaTiO3−δ additive, with respect to the dry Nafion content, were considered. The membrane with the lower amount of additive displayed the highest water affinity and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The synthesis of non-stoichiometric calcium titanate was carried out using a hydrothermal procedure followed by a calcination treatment, where Pluronic F127 was used as both structure-directing component and reducing agent to allow the formation of oxygen vacancies. This synthesis was carried out according to the details reported in our previous works [37,49].…”
Section: Synthesis Of Catio 3-δmentioning
confidence: 99%
“…The synthesis of non-stoichiometric calcium titanate was carried out using a hydrothermal procedure followed by a calcination treatment, where Pluronic F127 was used as both structure-directing component and reducing agent to allow the formation of oxygen vacancies. This synthesis was carried out according to the details reported in our previous works [37,49].…”
Section: Synthesis Of Catio 3-δmentioning
confidence: 99%
“…values obtained by weight. Anyhow, our previous results based on calorimetric measurements and dielectric spectroscopy [ 19 ] revealed that M5 sample has displayed the highest water affinity and conductivity, suggesting that an intermediate filler concentration (i.e., 5 wt.%) could be the best compromise. It can be assumed that the presence of oxygen vacancies in the perovskite structure guarantees the water trapping but a high dose of CTO (i.e., 10 wt.%) in the Nafion matrix can cause a lack of relative interactions between the polymer, additive and water to ensure the mobility of the protons.…”
Section: Resultsmentioning
confidence: 99%
“…A non-stoichiometric calcium titanate (CaTiO 3-δ , CTO) perovskite was prepared by a solvo-thermal procedure as reported in our previous papers [ 19 , 20 ], using a Pluronic F127 both as a structure directing agent and as a reducing component to obtain oxygen vacancies in the lattice of the perovskite. This procedure results in an orthorhombic CaTiO 3-δ perovskitewith an average crystallite size of about 145 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baglio et al [212] and Antonucci et al [213] focused their work on Nafion-TiO 2 and Nafion-SiO 2 respectively, to allow efficient operation at high temperature, above 100 • C. Both works claimed that the high temperature operating conditions were allowed by the better water retention and more uniform distribution of water across the composite membrane due to the presence of inorganic hygroscopic fillers inside the polymeric matrix. This resulted in reduced ohmic resistance and therefore better electrolyser performance [214]. The performance of composite membranes was better than that of Nafion membrane under high temperature and high pressure so the application of this technology is very promising especially when high electrical efficiency is required.…”
Section: Composite Membranes For Electrolysersmentioning
confidence: 99%